2020
DOI: 10.2478/ethemes-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Cost Accounting and Performance Measurement With the Purpose of Increasing the Competitiveness of Sports Organizations

Abstract: Dynamic business environment, rise in the share of overheads in total costs, strong competition on the global market and numerous other challenges that organizations are facing have imposed the need to reexamine the existing, design new costing methods and apply more appropriate management tools to improve management information basis, maintain and improve competitive advantage. In addition to traditional costing methods, organizations apply the methods adapted to the changing business environment, such as Act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Accurate forecasting of prices is a very challenging task due to the volatile and nonlinear nature of the financial stock markets (Jevtić et al, 2023). Researchers and academicians are still working on the best way in finance and economics to conquer this challenge (Makala & Li, 2021) In the literature, there are authors that focus their research on the stock price prediction (Shafiee & Topal, 2010;Jevtić et al, 2023;Čečević et al, 2023). Some authors in their research provided a review of available methods for gold price prediction (Zainal & Mustafa, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate forecasting of prices is a very challenging task due to the volatile and nonlinear nature of the financial stock markets (Jevtić et al, 2023). Researchers and academicians are still working on the best way in finance and economics to conquer this challenge (Makala & Li, 2021) In the literature, there are authors that focus their research on the stock price prediction (Shafiee & Topal, 2010;Jevtić et al, 2023;Čečević et al, 2023). Some authors in their research provided a review of available methods for gold price prediction (Zainal & Mustafa, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Monte Carlo method is widely used for stock price prediction in various industries and used by some groups of authors (Brodd & Djerf, 2018;Xiang et al, 2021;Jevtić et al, 2023;Čečević et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature [7] pointed out that the sports business cluster is a kind of economic network composed of sports enterprises and related services after studying tennis, soccer, and other leagues in Europe and America. The literature [8] applied the input-output model to the sports business, studied the intrinsic relationship between the sports business and the economy, and analyzed the effect of the inputs of economic factors on the development of the sports business. The literature [9] explored the changing functions of modern sports and suggested that the psychological, physical, social, and cultural functions in modern sports are gradually becoming a commercial need to satisfy the growth of monopoly capital.…”
Section: Introductionmentioning
confidence: 99%